Pengaruh Sikap Terhadap Minat Berwirausaha Mahasiswa Universitas Pandanaran - Sintya Oktarina; Dheny Indra Gunawan (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims to determine and analyze the influence of attitudes on the entrepreneurial interest of Pandanaran University students. This research uses a quantitative approach with the analytical method used is the multiple linear regression analysis method. The data source taken came from students at the Pandanaran University Entrepreneurship Study Program. Primary data in this research are questionnaire answers by respondents to questions regarding variables, namely attitude and interest in entrepreneurship. The data collection technique used by researchers is by distributing questionnaires containing several questions based on the variables to be studied. The research results show that the attitude variable has a positive and significant effect on the entrepreneurial interest variable.